New Tuberculostatic Agents Targeting Nucleic Acid Biosynthesis: Drug Design using QSAR Approaches - V. Bueno, Renata; C. Braga, Rodolpho; D. Segretti, Natanael; I. Ferreira, Elizabeth; H. G. Trossini, Gustavo; H. Andrade, Carolina (Current Pharmaceutical Design, 2014)
Worldwide, tuberculosis (TB) is the leading cause of death among curable infectious diseases. The emergence of multidrug resistant (MDR) and extensively drug resistant (XDR) TB is a growing global health concern and there is an urgent need for new anti-TB drugs. Enzymes involved in DNA and ATP biosynthesis are potential targets for tuberculostatic drug design, since these enzymes are essential for Mycobacterium tuberculosis growth. This review presents the current progress and applications of structure-activity relationship analysis for the discovery of innovative tuberculostatic agents as inhibitors of ribonucleotide reductase, DNA gyrase, ATP synthase, and thymidylate kinase enzymes, highlighting present challenges and new opportunities in TB drug design.
Keywords: QSAR